The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4269/ajtmh.14-0751
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall and Sloth Births in May, Q Fever in July, Cayenne, French Guiana

Abstract: Abstract. Q fever in French Guiana is correlated with the rainy season. We found a 1-to 2-month lagged correlation between Q fever incidence and the number of births of three-toed sloth. This result strengthens the hypothesis that the three-toed sloth is the wild reservoir of Q fever in French Guiana.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
1
7
0
Order By: Relevance
“…In a recent study, C. burnetii was detected by qPCR in the ticks, spleen, and stools of a dead three-toed sloth in Cayenne (84). In addition, the incidence of acute Q fever in Cayenne is correlated with the rainy season, and we observed a 1-to 2-month lag in the correlation between the incidence of acute Q fever and the number of births of three-toed sloths in Cayenne (85). Also, a retrospective study of an outbreak in a military camp in Cayenne in 2013 found that having carried a three-toed sloth in the arms in the month preceding symptoms was an independent risk factor for acute Q fever (unpublished data).…”
Section: The Different Epidemiological Profilessupporting
confidence: 46%
See 1 more Smart Citation
“…In a recent study, C. burnetii was detected by qPCR in the ticks, spleen, and stools of a dead three-toed sloth in Cayenne (84). In addition, the incidence of acute Q fever in Cayenne is correlated with the rainy season, and we observed a 1-to 2-month lag in the correlation between the incidence of acute Q fever and the number of births of three-toed sloths in Cayenne (85). Also, a retrospective study of an outbreak in a military camp in Cayenne in 2013 found that having carried a three-toed sloth in the arms in the month preceding symptoms was an independent risk factor for acute Q fever (unpublished data).…”
Section: The Different Epidemiological Profilessupporting
confidence: 46%
“…Rates of up to 20.8% seroprevalence for C. burnetii have been observed in macropods (140). In Cayenne, acute Q fever incidence is the highest in July, with a 2-month correlation following a peak in rainfall in May, which is the breeding season of the three-toed sloth, which is a probable wild reservoir of the infection (85).…”
Section: Seasonality Patterns and The Role Of Windmentioning
confidence: 99%
“…burnetii MST 17 has been detected in the spleen, stools, and ticks of a dead sloth near a recent outbreak site [ 34 ]. In addition, Q fever incidence was correlated with three-toed sloth birth numbers 1–2 months before, peaking during the rainy season in French Guiana [ 35 ]. However, for many animal species in French Guiana reproduction is related to the rainy season.…”
Section: The Singular Epidemiology Of Q Fever In French Guianamentioning
confidence: 99%
“…Several risk factors have been identified such as living near forested areas and practicing activities resulting in inhalation of aerosols of dusts [3]. In contrast, no link with classical sources of C. burnetii (cattle, sheep, or goat birth products) has been ever identified and a wild reservoir has been suspected [2,3,6,7].…”
Section: Introductionmentioning
confidence: 99%